(3fgL GdHdGZIs - (3Ydj Hf CHj WGdH,J (B40 (3g` s ((3eMeO Hf SYjO Hf GdMSjf GdYGeQj s)
(3ChdgG (B:s
(3CeG HYO GdMeO ddg GdPj LYd GdMeO KefkG dfYeGFg, heYGPG ef HdGFg aEfj cfJ aj YfahGf GdSf s
(3BNQgG (B:s
(3heG YSGg Cf jXgQ dfG HYV GdZehV, hjbY EdjfG HYO GdTPhP heG JhajbfG EdG HGddg hPdc aj QLH SfI CQHY eFg BNQ cJGH fgL GdHdGZI s
(3bQf GdfSN (B:s
(3GdbQf GdSGOSs
(3JHUQI GdYfhGf (B:s
(3TQM s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B295s
Keywords: (3GdCOHs